Underestimated Manipulative Roles of Mycobacterium tuberculosis Cell Envelope Glycolipids During Infection - Garcia-Vilanova, Andreu; Chan, John; Torrelles, Jordi B. (Frontiers in Immunology, 2019)
The M. tuberculosis cell envelope has been evolving over time to make the bacterium transmissible and adaptable to the human host. In this context, the M. tuberculosis cell envelope contains a peripheral barrier full of lipids, some of them unique, which confer M. tuberculosis with a unique shield against the different host environments that the bacterium will encounter at the different stages of infection. This lipid barrier is mainly composed of glycolipids that can be characterized by three different subsets: trehalose-containing, mannose-containing, and 6-deoxy-pyranose-containing glycolipids. In this review we explore the roles of these cell envelope glycolipids in M. tuberculosis virulence and pathogenesis, drug resistance, and further, how these glycolipids may dictate the M. tuberculosis cell envelope evolution from ancient to modern strains. Finally, we address how these M. tuberculosis cell envelope glycolipids are impacted by the host lung alveolar environment, their role in vaccination and masking host immunity, and subsequently the impact of these glycolipids in shaping how M. tuberculosis interacts with host cells, manipulating their immune response to favor the establishment of an infection.